Learning English Online: Endless Discovery - Peixoto, Summer (Issues in Language Instruction, 2018)
Keeping up with current trends and new developments in the realm of Computer-assisted Language Learning often invokes two opposite reactions. For those who juggle multiple projects, it may often seem like an arduous task with no clear, direct and visible benefit. “Why do I need to do this” might become a repeated mantra. For others, pursuing technology advancements may seem to be like it is simply part of the process; professional development is a teaching necessity. For teachers working in our Learning English Online lab (LEO), the pursuit of new technologies, knowledge, and professional development is a never ending, often curious and surprising, process of discovery